Biomarkers of PEGylated Liposomal Doxorubicin-Induced Hypersensitivity Reaction in Breast Cancer Patients Based on Metabolomics - Zhuang, Wei; Lai, Xiuping; Mai, Qingxiu; Ye, Suiwen; Chen, Junyi; Liu, Yanqiong; Wang, Jingshu; Li, Siming; Huang, Yanqing; Qin, Tao; Hu, Hai; Wu, Junyan; et al. (Frontiers in Pharmacology, 2022)
This study aimed to analyze and discuss the biomarkers of PEGylated liposomal doxorubicin (PLD) injection-induced hypersensitivity reactions (HSRs) in advanced breast cancer patients. Fourteen patients from Sun Yat-sen Memorial Hospital were included in the study between April 15th, 2020 and April 14th, 2021. Patient plasma was collected 30 min before PLD injection. HSRs were found to occur in a total of 9 patients (64.3%). No association was found between HSRs and various patient characteristics such as age, body surface area, anthracycline treatment history, IgE, and complement 3 and 4 (p > 0.05). Non-targeted metabolomics analysis of patient plasma was performed, and several metabolites showed significant association with HSRs. In particular, l-histidine (fold change = 91.5, p = 0.01) showed significantly higher levels in the immediate HSR group, while myristicin (fold change = 0.218, p = 0.003), urocanic acid (fold change = 0.193, p = 0.007), and d-aldose (fold change = 0.343, p = 0.003) showed significantly lower levels in the same group. In vivo experiments showed that exogenous histidine aggravated HSRs and increased IgE plasma levels in rats following the injection of PLD. Histidine can be decarboxylated to histamine by histidine decarboxylase. Histidine decarboxylase inhibitor 4-bromo-3-hydroxybenzoic acid improved symptoms and IgE levels in vivo. These findings suggested that l-histidine can be a potential biomarker for PLD-induced HSR. Moreover, an antihistamine drug, histidine decarboxylase inhibitor, or dietary histidine management could be used as potential preventive measures. Furthermore, metabolomics research could serve as a powerful method to explore biomarkers or uncover mechanisms of drug side effects.